Persepsi Pemustaka Terhadap Skill Pustakawan Dalam Penelusuran Sumber Informasi Di Perpustakaan Institut Agama Islam Negeri (IAIN) Batusangkar - Cut Afrina (Pustakaloka, 2022)
User perception is the argument given by the user from the results of observations and visions in the library, then analyzed according to the assumptions of each user of positive or negative perceptions of the librarian's skills in carrying out the process of searching for information sources in the library. The method used is qualitative with participatory objective observation on a social phenomenon that occurs in the library. The results of the study explain that the perception of users on the skills of librarians in searching for information sources at the library of the State Islamic Institute of Religion (IAIN) Batusangkar shows a negative perception of the skills of librarians in searching for information sources that suit the needs of users. The conclusion is that librarians must improve their Hard Skills and Soft Skills in tracing information sources.